Hydrogen-regulated chiral nanoplasmonics - Duan, Xiaoyang; Kamin, Simon; Sterl, Florian; Giessen, Harald; Liu, Na (Nano letters, 2016)
Chirality is a highly important topic in modern chemistry, given the dramatically different pharmacological effects that enantiomers can have on the body. Chirality of natural molecules can be controlled by reconfiguration of molecular structures through external stimuli. Despite the rapid progress in plasmonics, active regulation of plasmonic chirality, particularly in the visible spectral range, still faces significant challenges. In this Letter, we demonstrate a new class of hybrid plasmonic metamolecules composed of magnesium and gold nanoparticles. The plasmonic chirality from such plasmonic metamolecules can be dynamically controlled by hydrogen in real time without introducing macroscopic structural reconfiguration. We experimentally investigate the switching dynamics of the hydrogen-regulated chiroptical response in the visible spectral range using circular dichroism spectroscopy. In addition, energy dispersive X-ray spectroscopy is used to examine the morphology changes of the magnesium particles through hydrogenation and dehydrogenation processes. Our study can enable plasmonic chiral platforms for a variety of gas detection schemes by exploiting the high sensitivity of circular dichroism spectroscopy.